Are Online Job Postings Informative to Investors? - Gutiérrez, Elizabeth; Lourie, Ben; Nekrasov, Alexander; Shevlin, Terry (Management Science, 2020)
Human capital is a key factor in value creation in the modern corporation. Yet the disclosure of investment in human capital is scant. We propose that a company’s online job postings are disclosures made outside of the investor-relations channel that contain forward-looking information that could be informative to investors about future growth. We find that changes in the number of job postings are positively associated with changes in future performance and that this relation is stronger when postings likely represent growth rather than replacement. Consistent with job postings providing new information to the market, investors react positively to changes in the number of job postings. The market reaction to postings is stronger when firms are likely to be hiring for growth rather than replacement and for firms with low labor intensity (and therefore high marginal productivity of labor). This paper was accepted by Brian Bushee, accounting.